Implementasi Kebijakan Tata Kelola Pembiayaan Badan Layanan Umum Pada Universitas Islam Negeri - Jaenudin Jaenudin; Feni Arifiani; Iif Fikriyati Ihsani (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2022)
This paper explains the differences in the implementation of financing governance policies at universities that have an impact on the quality of management. The research was conducted on two leading Islamic universities in Indonesia, UIN Syarif Hidayatullah Jakarta and UIN Maulana Malik Ibrahim Malang. This article is based on the hypothesis that the combination of higher education self-financing with stricter restrictions on the state budget has caused higher education institutions to conduct workload studies on internal resources. The management of public service bodies that prioritize the principles of efficiency and productivity is part of a combination hypothesis that requires universities to implement business practices to improve services for the provision of educational services. Through an empirical approach, it was found that there was an increase in compliance with the policies of financing laws and regulations but there were distortions in the policy of centralization and decentralization of financing that had an impact on resource performance.Keywords: Public Service Agency; Financing Management; Islamic State University AbstrakTulisan ini menjelaskan perbedaan implementasi kebijakan tata kelola pembiayaan pada universitas berdampak kepada mutu manajemen. Penelitian dilakukan kepada dua perguruan tinggi Islam terkemuka, UIN Syarif Hidayatullah Jakarta dan UIN Maulana Malik Ibrahim Malang. Artikel ini didasarkan pada hipotesis kombinasi dari pembiayaan mandiri pendidikan tinggi dengan batasan lebih ketat pada anggaran negara telah menyebabkan institusi pendidikan tinggi untuk melakukan studi beban kerja pada sumber daya internal. Pengelolaan badan layanan umum yang mengutamakan prinsip efisiensi dan produktivitas merupakan bagian dari hipotesis kombinasi yang menuntut perguruan tinggi untuk menerapkan praktik-praktik bisnis untuk meningkatkan layanan penyediaan jasa pendidikan. Melalui pendekatan empiris ditemukan peningkatan kepatuhan terhadap kebijakan peraturan perundang-undangan pembiayaan namun terjadi distorsi dalam kebijakan sentralisasi dan desentralisasi pembiayaan yang berdampak kepada kinerja sumber daya.Kata kunci: Badan Layanan Umum; Manajemen Pembiayaan; Universitas Islam Negeri